PROSES PEMBELAJARAN BAHASA MANDARIN UNTUK SISWA SMP BHINNEKA TUNGGAL IKA YOGYAKARTA - , KARTINI ARNAWATI TELAUMBANUA, Panca Nugraha, B.Art., MTCSOL. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper entitled âThe process of teaching Mandarin for Students in Bhinneka Tunggal Ika Junior High School,Yogyakarta which is aimed to know how the process of teaching Mandarin in Bhinneka Tunggal Ika Junior High School.To collect data and information, the writer uses there methods that include observation, interview, questioner, and library study. Mandarin lesson in Bhinneka Tunggal Ika Junior High School is aimed to prepare the students and increase the ability in Mandarin. The process of teaching Mandarin in Bhinneka Tunggal Ika Junior High School is carried out well. The methods that Bhinneka Tunggal Ika used in teaching Mandarin